2013
DOI: 10.1111/ggi.12145
|View full text |Cite
|
Sign up to set email alerts
|

Nocturia among elderly men living in a rural area in Egypt, and its impact on sleep quality and health‐related quality of life

Abstract: Nocturia is widely prevalent among elderly men living in a rural area in Egypt. The adverse effect of nocturia on QoL is related to poor sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Nocturia has a negative impact on the QoL in some populations, while is well tolerated in others (Abdel Rahman & El Gaafary, 2014;Moreira et al, 2013;Oelke, Wiese, & Berges, 2014;Suekane et al, 2016). In the present study, the multivariate analysis showed association of nocturia with worst scores in the General Health, Social Functioning, Bodily Pain, Vitality and Physical Functioning domains.…”
Section: Discussionsupporting
confidence: 56%
“…Nocturia has a negative impact on the QoL in some populations, while is well tolerated in others (Abdel Rahman & El Gaafary, 2014;Moreira et al, 2013;Oelke, Wiese, & Berges, 2014;Suekane et al, 2016). In the present study, the multivariate analysis showed association of nocturia with worst scores in the General Health, Social Functioning, Bodily Pain, Vitality and Physical Functioning domains.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have reported similar results. A cross-sectional survey investigated the impact of nocturia on sleep quality and health-related QOL (SF-36) in 1200 elderly men (age, !60 yr) in Egypt [7]. Their results suggested that nocturia is an independent risk factor of poor sleep quality (OR, 5.08).…”
Section: Discussionmentioning
confidence: 97%
“…Although a negative association between nocturia and QOL has been reported, only few studies have evaluated the impact of nocturia and sleep disturbance on comprehensive QOL using SF-36 [3,[7][8][9][10]. This is the largest study evaluating the association of nocturia and sleep disturbance with QOL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations